PERANCANGAN SISTEM INFORMASI ANALISIS KUANTITATIF REKAM MEDIS RAWAT INAP DI RUMAH SAKIT BHAYANGKARA KOTA BENGKULU - Cici Lara Widiya; Yuda Syahidin; Sali Setiatin (INFOKES (Informasi Kesehatan), 2021)
This research aims to make design of system information design by quantitative analysis of medical records inpatient in Rumah Sakit Bhayangkara Kota Bengkulu.The method used in this research is qualitative research method which is a direct research method, such as data collection, field study and literature study, which is related to research problem, while software development using waterfall method with unified modeling language (UML) as design of software. Programming language used is PHP and database used is MySQL. Based on the research, various problems are found: quantitative analysis of medical records is not well computerized and reports have not been implemented properly. The suggestions given are: 1) the design of information system of quantitative analysis of medical record to optimize quantitative medical record analysis and recapitulation report of result of quantitative analysis, 2) maintain and develop information system of quantitative analysis of medical record and 3) follow up to doctors or an officer for completing an incomplete medical record form. Keywords: Design, system information, medical record, php and MySQL.